Systematic Literature Review of Complementary Food Hygiene Interventions on Child Health Outcomes. (14th June 2022) - Sivalogan, Kasthuri; Duong, Minh-Cam; Nguyen-Viet, Hung; Ramakrishnan, Usha; Young, Melissa
Abstract: Objectives: Despite known associations of contaminated food with enteric infections and diarrheal diseases, we have limited understanding about effective strategies to improve complementary food (CF) hygiene. We aim to conduct a systematic review to assess the effectiveness of CF hygiene interventions on caregiver and child health outcomes. Methods: Systematic review included experimental and quasi-experimental studies that assessed caregivers' food hygiene knowledge and practices, microbiological contamination in CF, and incidences of enteric disease in children. Review includes studies carried out in home/community settings with a control comparison and among caregivers of children 6 mo-5y. The search strategy was conducted in Cochrane, PUBMED, and Web of Science. Title, abstract, and full-text screening were conducted by two independent coders using Covidence. Results: 1, 773 studies were imported and after removal of duplicates and title/abstract screening, 40 studies were assessed for full-text eligibility. 24 studies, conducted in African and Asian countries, met the inclusion criteria; 6 studies had interventions that focused exclusively on CF hygiene while the rest integrated CF hygiene into broader nutrition or WASH interventions. Studies used behavioral change communication (BCC) strategies through home visits, group meetings, community campaigns, or media. Among the 6 studies, 3 examined microbial outcomes, 4 assessed caregivers' knowledge or behavior, no studies assessed children's diarrhea or enteric disease. Microbial contamination ( C. perfringens, E. coli, fecal coliform and KF-streptococcus ) levels were significantly reduced (p-value < 0.05) in all studies. Targeted complementary food hygiene behaviors outcomes significantly increased in 3 out of the 4 studies (ranging from 20–50% improvement). Conclusions: Most studies evaluating CF hygiene interventions used BCC strategies but it was difficult to identify their independent effects since they were often packaged within a broader interventions. Further attention is needed particularly in urban settings given the rise in individuals residing in urban settings with limited sanitation infrastructure. Funding Sources: Supported by contributors to the CGIAR Trust Fund and conducted by the Agriculture for Nutrition and Health Program.